Site-specific relaxase activity of a VirD2-like protein encoded within the tfs4 genomic island of Helicobacter pylori - Grove, Jane I.; Alandiyjany, Maher N.; Delahay, Robin M. (American Society for Biochemistry and Molecular Biology, 2013)
Four different type IV secretion systems are variously represented in the genomes of different Helicobacter pylori strains. Two of these, encoded by tfs3 and tfs4 gene clusters are contained within self-transmissible genomic islands. Although chromosomal excision of tfs4 circular intermediates is reported to be dependent upon the function of a tfs4-encoded XerD tyrosine-like recombinase, other factors required for transfer to a recipient cell have not been demonstrated. Here, we characterize the functional activity of a putative tfs4-encoded VirD2-like relaxase protein. Tfs4 VirD2 was purified as a fusion to maltose-binding protein and demonstrated to bind and nick both supercoiled duplex DNA and oligonucleotides in vitro in a manner dependent upon the presence of Mg2+ but independently of any auxiliary proteins. Unusually, concentration-dependent nicking of duplex DNA appeared to require only transient protein-DNA interaction. Although phylogenetically distinct from established relaxase families, site-specific cleavage of oligonucleotides by Tfs4 VirD2 required the nick region sequence 5′-ATCCTG-3′ common to transfer origins (oriT) recognized by MOBP conjugative relaxases. Cleavage resulted in covalent attachment of MBP-VirD2 to the 5′-cleaved end, consistent with conventional relaxase activity. Identification of an oriT-like sequence upstream of tfs4 virD2 and demonstration of VirD2 protein-protein interaction with a putative VirC1 relaxosome component indicate that transfer initiation of the tfs4 genomic island is analogous to mechanisms underlying mobilization of other integrated mobile elements, such as integrating conjugative elements, requiring site-specific targeting of relaxase activity to a cognate oriT sequence.